Journey and Life Purpose in Aleph by Paulo Coelho - Jessica Nathary Thenny Soendayana (Passage, 2016)
This research paper entitled  “Journey and Life Purpose in Aleph by Paulo Coelho” aimed toanalyze the kinds of journey presented in the selected novel and the way in which shape themain character’s life purpose. Using a descriptive qualitative method, this study employs content analysis approach which is framed with theory from Bodart, Barrineau, and Flamino (2011) to interpret and understand the journey in the selected novel. The findings show that there are two kinds of journey presented in the novel, which are literal and metaphorical journey. Through his literal and metaphorical journey, the main character achieves his life purpose of spirituality and self-transcendence. From findings, it can be seen that journey isconsidered as an essentials process of life to be experienced by people. Keywords: Aleph, Paulo Coelho, journey in literature, life meaning, life purpos